Spin topology in metallic magnets - Lim, Yong Xin (2016)
In this thesis, the topic on spin topology on metallic material is to shed light on the magnetic topology in the form of skyrmions generated from the addition of two interfacial Dzyloshinskii-Moriya interaction (DMI). The task was to identify parameters necessary for skyrmion nucleation, as well as to increase skyrmion density if skyrmions could be found. To aid in this endeavor, magnetic force microscopy imaging, superconducting quantum interference device (SQUID) magnetization loops, as well as MUMAX simulation was used to gain an understanding of materials needed to go about tackling the task.